Bis(4-pyridyl)mercury – a new linear tecton in crystal engineering: coordination polymers and co-crystallization processes1. Issue 29 (7th August 2015) - Mocanu, Teodora; Raţ, Ciprian I.; Maxim, Catalin; Shova, Sergiu; Tudor, Violeta; Silvestru, Cristian; Andruh, Marius
<x xml:space="preserve">Abstract</x> Three new coordination polymers have been obtained using bis(4-pyridyl)mercury (py2Hg) as a spacer: [Cu(Hmea)2(py2Hg)](ClO4)2·2(py2Hg) (1), [Cu2(pa)2(py2Hg)(ClO4)2]·0.5(py2Hg)·H2O (2), and [Cu2(pa)2(py2Hg)2](BF4)2 (3) (Hmea = monoethanolamine; Hpa = propanolamine).